SISTEM INFORMASI PENGAJUAN CUTI PEGAWAI BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER(Studi Kasus Dinas Ketahanan Pangan) - Klaudiana Wea; Kristianus Jago Tute; Elvira Esperanza Sala (Jurnal Riset Teknik Komputer, 2025)
Submitting leave is a formal process carried out by an employee or staff to request permission to be absent from work for a certain period of time. At the Food Security Service, leave submission is still done manually, where an employee must fill out a form that still uses paper media, and submit it directly to the superior (HRD), to obtain approval. The purpose of this study is to design and develop an online leave submission information system using a web-based codeigniter framework, which can provide convenience for employees in submitting leave, as well as make it easier for management to monitor, manage, and provide leave approval more efficiently. The main purpose of the codeigniter framework is to facilitate easy and fast application development for system developers.